Study on the influence of moving contact speed on the breaking characteristics of DC miniature circuit breakers - Jie Zhang; Zhouqian Yao; Wei Zhang; Bowang Wang; Yingbo Huang (AIP Advances)
The moving contact speed of DC miniature circuit breakers (MCBs) directly affects the arcing characteristics in the arc chamber, thus affecting their breaking capacity. Based on this, this paper studies the arcing characteristics in the arc chamber under different moving contact speeds. Through simulation, the temperature, velocity, and pressure distribution characteristics in the arc chamber are obtained. It is shown that with the increase in moving contact speed, the arc is more easily stretched and can be cut by the splitter plate in time. However, as the moving contact speed increases, the arc temperature will also increase. There is an optimal value for the moving contact speed, which is more reasonable between 129 and 144 rad/s. This study has reference significance for improving the breaking capacity and reliability of DC MCBs.